General joint hypermobility in temporomandibular joint disease; clinical characteristics, biomarkers, and surgical aspects - Mattias Ulmner; Rachael Sugars; Aron Naimi-Akbar; Janne Elin Reseland; Bodil Lund (Heliyon, 2023)
Objectives: This study aimed at identifying biomarkers in the temporomandibular joint (TMJ) synovial tissue analysing 28 extra cellular matrix proteins in TMJ diseased patients, classified with either general joint hypermobility (GJH) or normal joint mobility (NJM), and to compile clinical and protein characterisation to reveal potential surgical predictive factors. Study design: A prospective observational cohort study including 97 consecutive patients scheduled for TMJ surgery was performed. Joint mobility and several other predefined clinical variables were recorded. Synovial tissue was harvested during surgery followed by examination using multi-analytic profiling. A multivariate quantile regression model was used for analysis purposes. Results: The GJH/NJM ratio was 2:5. The GJH cohort were younger (P = 0.001) and more likely to be women (P = 0.026) compared to the NJM cohort. None of the protein concentrations could be correlated to joint mobility in the multivariate regression model, but often to the variable TMJ diagnosis. The surgical outcome after the six-month follow-up were equal between GJH and NJM patients. Conclusions: GJH was more common in the study cohort compared to general population frequencies, but GJH was not a negative factor for surgical outcome. Young age and female gender correlated to GJH. No TMJ biomarkers were GJH specific, and the results suggested that TMJ diagnosis more strongly correlated to the protein profile compared to GJH and the other investigated variables.